2006
DOI: 10.1111/j.1467-842x.2006.tb00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Now, later or never? Challenges associated with hepatitis C treatment

Abstract: Results:The average age of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 9 publications
(11 reference statements)
1
26
0
Order By: Relevance
“…McNally et al [8] proposed that confidence in treatment efficacy was the main consideration in deciding to undertake treatment. Underscoring the contextual influences involved in making treatment decisions, Ogawa and Bova [73] suggested that treatment decisions in former IDU were complicated by fears that self injecting interferon could reintroduce the use of syringes in a way that might threaten their control over their injecting drug use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…McNally et al [8] proposed that confidence in treatment efficacy was the main consideration in deciding to undertake treatment. Underscoring the contextual influences involved in making treatment decisions, Ogawa and Bova [73] suggested that treatment decisions in former IDU were complicated by fears that self injecting interferon could reintroduce the use of syringes in a way that might threaten their control over their injecting drug use.…”
Section: Resultsmentioning
confidence: 99%
“…Between 70% and 85% of those initially infected fail to clear the virus [5-7]. Hepatitis C treatments are available, but uptake remains low even in countries such as Australia, where treatment is available at low cost to eligible patients [8,9]. Thus, most people with hepatitis C infection face the prospect of lifelong chronic infection.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with female, HCV mono-infected patients declining therapy significantly more often than their male counterparts (Khokhar & Lewis, 2006). Similarly, men were found to be twice as likely to be treated for HCV as women (McNally, Temple-Smith, Sievert, & Pitts, 2006). The reasons why women decline HCV treatment more often than men is unclear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers are small because of the numerous deterrents to HCV treatment, which include side effects, the rigorous nature of treatment, and the impact of treatment on work and family (Doab et al, 2005; McNally et al, 2006; Wilson et al, 2010). Additionally, people with HCV may face competing health and social concerns that impede their access to care and treatment, including poverty (Edlin et al, 2005; McNally et al, 2006), unemployment, lack of stable housing (Edlin et al, 2005; Grebely et al, 2008) and comorbidity such as mental health problems (Weiss et al, 2012). Given the social and economic disadvantages experienced by Aboriginal Australians, these barriers could be exacerbated (Hunter, 2007).…”
Section: Introductionmentioning
confidence: 99%